Kazakh Initiatives on Cooperation with European Union - R. S. Kurmanguzhin (Vestnik MGIMO-Universiteta)
The author of this article presents initiatives of the Republic of Kazakhstan to develop cooperation with the European Union that was initiated through 2000 - 2009. In 2000 the Republic of Kazakhstan proposed to EU Comment cooperation doctrine in Central Asia. The purpose of the doctrine lied in expanding cooperation in the areas of trade, economy and investment; in granting access to commodities and services from European markets; in developing collaboration in the areas of energy, transport, communication, finance and banking. In 2006 Kazakhstan introduced a new set of prepossess to the new European Union Strategy for Central Asian 2007-2013 that was developed under the chairmanship of Germany of the EU in the first half of 2007. The Strategy covered areas of cooperation such as regional integration, economic development, democratization, energy and security. In 2008 under the instructions of the President of Kazakhstan Ministry of Foreign Affairs in cooperation with other ministries developed a state programme "Path to Europe" for 2009 - 2011, which aided the priorities of cooperation between Kazakhstan and the European Union. "Path to Europe" has become a key initiative of the Kazakh foreign policy that was successfully implemented, as well as the most important document aimed at modernization of the national economy and the Kazakh society. In the beginning of2009 using the accumulated positive experience of cooperation with the EU and experience of a number of countries in Europe and Asia, Kazakhstan devised and submitted a concept of a new treaty which was supposed to replace the Partnership and Cooperation Agreement of 1995. The Republic of Kazakhstan's influence eventually persuaded the European Union to agree on the necessity of devising the Enhanced Partnership and Cooperation Agreement.